2008
DOI: 10.1071/sb07028
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structuring in the spotted gum complex (genus Corymbia, section Politaria)

Abstract: Spotted gums (genus Corymbia, section Politaria) occur as a species replacement series along the eastern seaboard of Australia, their distributions marked by regions of disjunction and sympatry. Their taxonomy remains controversial, with species assignment often challenging and reliant on knowledge of geographic origin as well as subtle morphological or leaf-oil variation. In the present paper, we explore a classification for spotted gums, without assuming predefined geographic or taxonomic groups but instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…However, when co-occurring, such closely related species are often poorly differentiated, e.g. Corymbia (Ochieng et al 2010;Shepherd et al 2008a), Eucalyptus (Holman et al 2003;Jones et al 2002), although there are exceptions which argue for barriers to gene flow, e.g. Eucalyptus (McGowen et al 2001) and Melaleuca (Broadhurst et al 2004).…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when co-occurring, such closely related species are often poorly differentiated, e.g. Corymbia (Ochieng et al 2010;Shepherd et al 2008a), Eucalyptus (Holman et al 2003;Jones et al 2002), although there are exceptions which argue for barriers to gene flow, e.g. Eucalyptus (McGowen et al 2001) and Melaleuca (Broadhurst et al 2004).…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%
“…Evolution at lower taxonomic levels in Eucalyptus-species complexes A number of nuclear microsatellite studies are also revealing an absence of consistent differentiation between closely related, co-occurring species in Corymbia (Ochieng et al 2008(Ochieng et al , 2010Shepherd et al 2008a) and in Eucalyptus (Holman et al 2003;Hudson 2007;Le et al 2009). The spotted gums (genus Corymbia, section Politaria) show a species replacement series along the eastern seaboard of Australia, with distributions marked by regions of disjunction and sympatry.…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%
“…The development of microsatellite primers for eucalypt taxa (Brondani et al 1998(Brondani et al , 2006Byrne et al 1996;Glaubitz et al 2001;Jones et al 2001;Ottewell et al 2005;Shepherd et al 2006;Steane et al 2001;Thamarus et al 2002) opened the door for reliable genome-wide genotyping of a relatively large number of samples. Microsatellite markers gave researchers the power to examine genetic relationships within and among populations of one (e.g., Butcher et al 2009;Elliott and Byrne 2003;Jones et al 2007;Payn et al 2008;Rathbone et al 2007;Walker et al 2009; see also Byrne 2008 and references therein) or a few closely related species (e.g., Holman et al 2003, Le et al 2009, Shepherd et al 2008. While microsatellites were developed initially for mapping and population genetic studies, Ochieng et al (2007b) found them helpful for phylogenetic resolution of eucalypt genera.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shepherd et al (2008) suggested that there was insufficient distinction between the northern taxa, including C. henryi, C. variegata and C. citriodora, to justify their treatment as a single species and that they were better viewed as two or three sub-species or races.…”
Section: Discussionmentioning
confidence: 99%